Elsa Morante. Mito e letteratura - Dell'Aia, Lucia (Harpocrates, 2021)
Collected in this volume are essays that address the various declinations of the presence of myth in the overall experience of Elsa Morante's writing from different theoretical and critical perspectives. Focusing on the distinction between myth, mythology and demythologizing, the book tries to go to the heart of the interpretation of the realistic and mythical choice of the great writer's creations. The book closes with a lyrical and testimonial prose by Gabriella Sica. The volume is part of the study projects of the international research group Harpocrates.